(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: Anal cancer is a rare tumor whose incidence is influenced by sexual behavior and biological and social vulnerabilities. A likely explanation for the increased incidence in recent decades in developing countries is the low coverage or nonexistence of screening programs for precursor lesions. Objectives: Address the combined methods that make up the basic tripod in the Unified Health System (SUS) for the evaluation of the anal canal and diagnosis of cancer and/or its precursor changes caused by HPV, guiding the collection and technical processing of samples in public health services. Methods: This is a selective review of the literature of qualitative and exploratory nature, using publications available in the public interface of the “Portal de Periódicos Capes”. Results: There are no programs for screening of precursor lesions of anal cancer, but the application of resources for diagnosis of early changes is based on the success obtained with the screening of precursor lesions of cervical cancer, since the pathologies share cytohistological, etiological similarities, risk factors, techniques for diagnosis and health professionals. This article reviews the available diagnostic methods and the possible treatments for anal precursor lesions to prevent progression to cancer. With this material, health professionals can benefit from the guidelines and then exercise relevant role in the prevention of cancer. Conclusion: It is possible to incorporate a policy of early diagnosis into the SUS to qualify and expand initiatives to promote and care for people.